2015
DOI: 10.1159/000441517
|View full text |Cite
|
Sign up to set email alerts
|

Subpubic Arch Angle and Mode of Delivery in Low-Risk Nulliparous Women

Abstract: Objective: To assess whether subpubic arch angle (SPA) measurement before labor onset can predict labor outcome among low-risk pregnant women. Methods: 3D ultrasound volume was transperineally acquired from a series of nulliparous women with uncomplicated pregnancy at term before the onset of labor. SPA was measured offline using Oblique View Extended Imaging (OVIX) on each volume performed by an investigator not involved in the clinical management. Labor outcome was prospectively investigated in the whole stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 10 publications
0
20
1
Order By: Relevance
“…However, in the present study, the distribution of spontaneous vaginal and vaginal operative deliveries was similar for the microcephalic fetuses and the fetuses with a normal head circumference. This finding suggests that additional factors in labor process may decrease the potential gain of small head circumference, such as a narrow pubic arch angle and small maternal stature, which correlate with a small pelvic diameter [21,22]. Both these factors have been associated with a higher rate of instrumental vaginal delivery.…”
Section: Discussionmentioning
confidence: 86%
“…However, in the present study, the distribution of spontaneous vaginal and vaginal operative deliveries was similar for the microcephalic fetuses and the fetuses with a normal head circumference. This finding suggests that additional factors in labor process may decrease the potential gain of small head circumference, such as a narrow pubic arch angle and small maternal stature, which correlate with a small pelvic diameter [21,22]. Both these factors have been associated with a higher rate of instrumental vaginal delivery.…”
Section: Discussionmentioning
confidence: 86%
“…Within a general population of women with singleton pregnancies close to term, SPA width has shown a normal distribution ranging from 65.6 to 131.6° and a mean value just below 110° [16]. A narrow SPA obtained on 3D ultrasound has been associated with an increase in the incidence of prolonged labor [16], persistent occiput posterior at birth, and UOI among nulliparous women [17,18]. In the current study, in a population at high risk for cephalopelvic disproportion, SPA width was demonstrated to predict an abnormal course of labor with 89% sensitivity and an over 70% positive predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, the use of ultrasound has proved to be reliable in assessing the subpubic arch angle (SPA) [11,12], whose size is related to the transverse diameter of the birth canal [13]. Some independent studies have shown that, in the general population, a narrow SPA at antepartum ultrasound is associated with prolonged labor [14][15][16] and an increased risk of obstetric intervention [17,18]. The aim of our study was to assess the correlation between the SPA and the outcome of labor in a group of women at higher risk for obstructed labor, including nulliparous women with large-for-gestationalage (LGA) neonates.…”
Section: Correlation Between Subpubic Arch Angle and Mode Of Deliverymentioning
confidence: 99%
“…Despite the strong correlation with adverse obstetrical outcome, it should be highlighted that the accuracy of SPA in the prediction of complications remains limited, 83 , 84 and should not be used alone for clinical decision making.…”
Section: Obstetricsmentioning
confidence: 99%
“…The SPA is then measured by the two-line function ( D ) (reproduced from Youssef et al with permission). 84 …”
Section: Figurementioning
confidence: 99%